Lighting Performance at two Different Types of Mosques in Batu Pahat - Roslin, Nur Iffah Nabilah; Tami, Hannifah (Recent Trends in Civil Engineering and Built Environment, 2021)
A domed mosque has lower illuminance value compare to a pitched roof mosque. This study aims to identify the attribute of lighting performance in the mosque and determine the lighting performance via a comparative study at prayer hall of two different mosques design. It aims to ensure that lighting levels are compatible and meet the standards. Data from Lux meter readings have been taken according to the drawing layout. OriginPro software was being used to create contours of illuminance level. Meanwhile, DiaLux software was being used to design lighting system and interiors of the prayer halls. The data obtained were compared with the recommendation from Malaysian Standard and European Standard. Natural lighting for both mosques did not achieve the recommendation value of both standards. For artificial lighting, both mosques only comply to Malaysian Standards. Mosque with dome need to depend on artificial lighting to improve the appearance in the prayer hall. Recommendations that can be made including substitute LED pendant light at the centre of the domed mosque and install transparent roof at certain area. It would be able to increase the illuminance level at the prayer hall and enhance visual comfort among visitors.